The Role of Problem-Based Learning Approach in Teaching and Learning Physics: A Systematic Literature Review - Nicholus, Gumisirizah; Muwonge, Charles Magoba; Joseph, Nzabahimana (F1000Research, 2023)
Problem-based learning (PBL) is a learner-centered method in which complex real-world problems are used to stimulate students thinking and problem-solving abilities during the teaching and learning process. This systematic review aimed to reveal the role of the PBL approach in teaching and learning physics. Relevant articles for the review were sourced from Scopus and Web of Science using keywords such as “problem-based learning” and “PBL in physics” education” as search terms. This search yielded 376 results. Thirty-six articles were included in the analysis after passing a crucial condition of empirically investigating the effect of PBL in teaching and learning physics. Only three of these articles did not show a positive effect; others have shown a positive lead of PBL towards improving academic achievement, attitude to learn physics, problem-solving, critical and creative thinking abilities, cooperative learning enhancement, mental model development, and science process skills attainment. Therefore, the review offers important pointers to various classroom environments and activities that ignite learners’ thinking. Thus, it help policymakers to select and maintain the best methodology that promotes high students’ academic achievement levels.
Keywords: Problem-based learning; Students’ academic achievement; Attitude in Physics; Systematic review